Design Of Multi-Service Access Node (MSAN) Roadside Cabinet Battery Compartment Lock - Zulkifli, Aliff Danial (Universiti Sains Malaysia, 2018)
Lately, the increasing of stealing Multi-Service Access Node (MSAN) compartment of Telekom Malaysia (TM) roadside cabinet cases causing huge losses for them. These crime cases are keep increasing though police have taken the action to avoid this case happen again. This case not only caused thousand ringgit losses for TM but also affected the phone and internet networking. It will ruin TM if they cannot satisfy their customer through their services. To solve this issue, a study has been carried out which is the study of design and development of locking mechanism of MSAN battery compartment. This study uses to investigate and analyse the reason why current security mechanism are not good enough to prevent the theft to steeling the batteries compartment on MSAN road cabinet. From the information and collected data, a few concept designs have come out and be compared to choose the most efficient and reliable concept to be develop. The final will be test and analyse so it can meet the design specification. All the concept detail and specification have been discussed with supervisor, Mr. Mohzani and the TM’s team. The material selection for the design have been discussed to ensure it can meet the product function.